Blood Parameters as Indicators of Upper Airway Obstruction in Children With Adenoid or Adenotonsillar Hypertrophy. Issue 3 (May 2015) - Simsek, Gokce; Karacayli, Ceren; Ozel, Aysenur; Arslan, Bengi; Muluk, Nuray Bayar; Kilic, Rahmi
<x xml:space="preserve">Abstract</x> Adenotonsillar hypertrophy (ATH) is the most common cause of obstructive sleep apnea in children. This study aimed to evaluate the blood parameters of children with ATH who underwent surgery.